Market Your Way to Growth : 8 Ways to Win. - Kotler, Philip; Kotler, Milton (New York : Wiley, 2012)
Marketing guru Philip Kotler and global marketing strategist Milton Kotler show you how to survive rough economic waters With the developed world facing slow economic growth, successfully competing for a limited customer base means using creative and strategic marketing strategies. Market Your Way to Growth presents eight effective ways to grow in even the slowest economy. They include how to increase your market share, develop enthusiastic customers, build your brand, innovate, expand internationally, acquire other businesses, build a great reputation for social responsibility.
Chapter 4: Grow by Innovating New Products, Services, and ExperiencesConclusion; Chapter 5: Grow by International Expansion; Engaging in Foreign Direct Investment; Engaging in Export; Conclusion; Questions; Chapter 6: Grow by Mergers, Acquisitions, Alliances, and Joint Ventures; Conclusion; Questions; Chapter 7: Grow by Building an Outstanding Reputation for Social Responsibility; Conclusion; Chapter 8: Grow by Partnering with Government and NGOs; Conclusion; Questions; Epilogue; Index.
Print version record.
Includes bibliographical references (pages 201-206) and index.
John Wiley and Sons
Keywords: Marketing; Customer relations -- Management; Relationship marketing; Marketing; Marketing; Marketing relationnel; marketing; BUSINESS & ECONOMICS -- Distribution; BUSINESS & ECONOMICS -- Marketing -- General; Customer relations -- Management; Marketing; Relationship marketing; Marketing; Beziehungsmarketing; Erfolgsfaktor